Cluster Analysis of The Potential Palawija Plants in Central Java Province - Mujiono Mujiono; Eko Sumartono (Jurnal Social Economic of Agriculture, 2022)
This study aims to research the potential of secondary crops in Central Java exploitation cluster analysis (non-hierarchical) and maping employing a geographic information system. processing was allotted using SPSS 15.0 and Arcgis 10. 2. The results showed that Sukoharjo, Kudus, Demak, Pekalongan, Pemalang, Tegal, Brebes, Magelang town, Surakarta City, Salatiga City, city City, Pekalongan City, Tegal City had low potential (cluster 3), whereas Cilacap, Banjarnegara, Kebumen, Purworejo, Wonosobo, Boyolali, Wonogiri, Grobogan, Blora, Rembang, Temanggung, High Potential are classified as medium. The regions with high potential for secondary crops are Banyumas, Purbalingga, Magelang, Klaten, Karanganyar, Sragen, Pati, Semarang, Kendal, and Batang.